Pengaruh Kualitas Produk dan Customer Experience Terhadap Kepuasan Pelanggan Brand Erigo - Ema Umiatul Chusna; Ita Rifiani Permatasari; Mohammad Maskan (INDO PUBLISHING, 2025)
Competition in the digital fashion industry drives companies to ensure customer satisfaction as a key element of business sustainability. Erigo is one of the local Indonesian brands that has successfully entered the international market. As an active brand on the Shopee e-commerce platform, Erigo faces challenges related to customer complaints about product quality and shopping experience. The study aims to determine and analyze the extent of the influence of these two variables on customer satisfaction of Erigo brand.This study employed a quantitative approach with a survey method. The sampling technique used was non-probability sampling, specifically purposive sampling. The study obtained 100 respondents who had purchased Erigo products through Shopee. The data were collected through an online questionnaire and analyzed using multiple linear regression, assisted by statistical software, to examine both partial and simultaneous effects between variables.The findings showed that product quality and customer experience had a positive influence on customer satisfaction, both partially and simultaneously. The result of the partial test and multiple linear regression analysis showed that the calculated t-value was greater than the table t-value, which was 2.627 > 1.66071. The Coefficient of determination was 0.618, which meant that 61.8% of the variation in customer satisfaction could be explained by product quality and customer experience. Meanwhile, the remaining 38.2% was influenced by other factors not examined in this study.It can be concluded that product quality and customer experience positively influence customer satisfaction. Erigo is advised to enhance emotionally engaging product designs and strengthen digital interaction and customer service to create a more optimal shopping experience.